2008
DOI: 10.1142/s0219198908001959
|View full text |Cite
|
Sign up to set email alerts
|

Coalition Formation in Straddling Stock Fisheries: A Partition Function Approach

Abstract: In this paper the management of straddling fish stocks is approached through a coalition game in partition function form. A two-stage game is applied, assuming ex ante symmetric players and the classical Gordon-Schaefer bioeconomic model. It is shown that the game is characterized by positive externalities — the merger of coalitions increases the payoffs of players who belong to other coalitions. A key result is that, apart from the case of two players, the grand coalition is not a Nash equilibrium outcome. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 11 publications
2
54
2
3
Order By: Relevance
“…6 Apart from the situation when the local common consists of just two herdsmen (i.e., N 5 2), a stable coalition simply does not exist (see the Appendix). The same result is also the outcome of the well-known global pollution model by Barrett (1994), and the (static) Gordon-Schaefer fishery model by Pintassilgo and Lindroos (2008).…”
Section: (4)supporting
confidence: 74%
See 1 more Smart Citation
“…6 Apart from the situation when the local common consists of just two herdsmen (i.e., N 5 2), a stable coalition simply does not exist (see the Appendix). The same result is also the outcome of the well-known global pollution model by Barrett (1994), and the (static) Gordon-Schaefer fishery model by Pintassilgo and Lindroos (2008).…”
Section: (4)supporting
confidence: 74%
“…In their paper it is simply assumed that the coastal state fleet ex ante is more cost efficient than the distant water states fleets (see also Kaitala and Pohjola 1988;Pintassilgo 2003;Pintassilgo and Lindroos 2008). As a consequence, in a stable coalition, the most cost-efficient nation is the only active coalition member, and stability is ensured by sharing the benefits with all other coalition members.…”
Section: Introductionmentioning
confidence: 99%
“…There is consensus in the literature on international fisheries management that countries with shared resources benefit from regional cooperation to conserve and manage those resources (Lindroos and Pintassilgo 2008;Rahikainen et al 2008;Bailey et al 2010;Hannesson 2011;Walker and Weikard 2016). Knowing that cooperation can be beneficial, it is important to understand the wider political context that has, in many cases, undermined the potential for cooperation in the first place.…”
Section: Internal Stability Of Fisheries Agreementsmentioning
confidence: 99%
“…Over the last decade, studies have adopted the static noncooperative game to address coalition formation when the number of agents sharing a fishery is greater than two, including Pintassilgo (2003), Kronbak and Lindroos (2006), Pintassilgo and Lindroos (2006), Kaitala and Lindroos (2007), and Pintassilgo et al (2008). Kaitala and Lindroos (2007) argued that the advantage of static over dynamic games is that analytical results of static games are easier to derive and interpret.…”
Section: Introductionmentioning
confidence: 99%
“…Using the static Cournot game combined with the classical Gordon-Schaefer model for homogenous fishing countries, Pintassilgo and Lindroos (2006) have, however, demonstrated that a non-cooperative solution is the inevitable outcome when the number of agents is more than two, and the grand coalition is a Nash stable equilibrium outcome only if there are two countries sharing a fish stock. This outcome results because the attraction of free riding is too great for free riders.…”
Section: Introductionmentioning
confidence: 99%